A Brief Study and Exploration of the Detailed Concepts of Social and Economic Cooperation with the Limited Opinions of Cooperative Economists on the Cooperation Principles Mansour Mozaffary (London Journal of Research In Management & Business, 2026)
Background and Objective In this topic and research, several concepts of “cooperation” have been mentioned and presented with the opinions of economic scientists with more themes and numerous concepts, but rather the aim is to observe several specific opinions of economic experts.Method: It is derived from the method of content ratio coefficient (CVR) and content index (CVI) and in such a way that it has taken examples from the opinions of cooperative economists and in another method, it has also taken several cases from the history of economic ideas and economic institutions.Findings: The meaning and concept of cooperation have been intuitively presented to researchers in various forms and forms, and cooperation has been completely raised from a general concept to a specific concept, namely cooperative economics, and another finding is that with the economic and centralized tendency, namely cooperatives, the manifestation and form of economic and social has been achieved simultaneously.Conclusion:Based on the research findings and initial themes, basic concepts and theories of economic scientists, it is evident that the presentation of an economic and social system is completely dependent on cooperation and collaboration, especially unity, and in the end, if there is a disruption, it will originate from the lack of unity and unity of individuals.
Keywords: cooperation; Cooperative; Cooperative Economy; Economy